The Relationship between Menopause and Depression in Padang - Arde Hidayat; Ariadi Ariadi; Firdawati Firdawati (Andalas Obstetrics And Gynecology Journal, 2021)
Objectives: to analyze the relationship between menopause and depression in PadangMethods : This type of research is an analytical observational with a comparative cross sectional approach that looks at the relationship between menopause and depression incidence. The research was conducted in the working area of the Padang City Health Center from April to June 2020. The instrument used in this study was the Hamilton Depression Rating Scale (HDRS / Ham-D) which was used to measure the level of depression and a questionnaire to ask questions related to the characteristics of the respondents.Results: A study was conducted on 170 people consisting of 85 respondents who had menopause and 85 respondents who had not yet menopause. Conclusion: As many as 50 (58.8%) menopausal respondents experienced depression and 35 (41.2%) respondents did not experience depression. There is a relationship between menopause and depression (p <0.05). There was a relationship between age, current medical history, income, occupation, and education level with the incidence of depression (p <0.05). There is no relationship between menopause duration, marital status, and BMI with depression incidence (p> 0.05)Keywords: depression, Hamilton Depression Rating Scale , menoupause